Having Your Day in Court: Judicial Opportunity and Tactical Choice in Anti-GMO Campaigns in France and the United Kingdom. (January 2014) - Doherty, Brian; Hayes, Graeme
Investigating the recent direct action campaigns against genetically modified crops in France and the United Kingdom, the authors set out to understand how contrasting judicial systems and cultures affect the way that activists choose to commit ostensibly illegal actions and how they negotiate the trade-offs between effectiveness and public accountability. The authors find evidence that prosecution outcomes across different judicial systems are consistent and relatively predictable and consequently argue that the concept of a "judicial opportunity structure" is useful for developing scholars' understanding of social movement trajectories. The authors also find that these differential judicial opportunities cannot adequately account for the tactical choices made by activists with respect to the staging of covert or overt direct action; rather, explanations of tactical choice are better accounted for by movement ideas, cultures, and traditions.